Ammonia-modulated reversible gel–solution phase transition and fluorescence switch for a salicylhydrazide-based metal–organic gel. Issue 49 (15th June 2017) - Lu, Shu-Mei; Huang, Jian-Cai; Liu, Guo-Ting; Lin, Zhi-Wei; Li, Yan-Tong; Huang, Xi-He; Huang, Chang-Cang; Wu, Shu-Ting
Abstract : A fluorescence metal–organic gel was studied with its reversible gel–solution phase transition and fluorescence switch by the modulation of ammonia. Abstract : Based on a multi-dentate salicylhydrazide-derived ligand, a Zn-contained metal–organic gel that could stand for months has been prepared. The driving force within the supramolecular assembly was discussed by studying the gelation conditions, optical spectra, dynamic rheology and mass spectra. These studies revealed that both the coordination bonds and hydrogen bonds participate in the supramolecular assembly. In addition, electrostatic force also played as a key role in stabilizing the gel phase. The charge nature of the colloidal particle is negative charged. Consequently, the xerogel shows significant adsorption behavior that favors positively charged dye molecules, such as methyl violet and methylene blue. The title gel exhibits gelation-induced fluorescence enhancement property. When the gel was exposed to ammonia vapor, a gel–solution transition occurred, accompanied by a great weakening of fluorescence. The phase transition and fluorescence switching were found to be reversible for at least seven cycles. The mechanism involved was studied and discussed.